Using Artificial intelligence to evaluate skill performance of some karate skills - Hayder Nazar Jawoosh; Dr.Abeer Dakhil; dr. Muhammed Asim Muhammed; dr. Mazin Hadi Gizar (physical education and sport sciences college for women/ Baghdad University, 2022)
Human beings are starting to benefit from the technology revolution that witness in our time. Where most researchers are trying to apply modern sciences in different areas of life to catch up on the benefits of these technologies. The field of artificial intelligence is one of the sciences that simulate the human mind, and its applications have invaded human life. The sports field is one of the areas that artificial intelligence has been introduced. In this paper, artificial intelligence technology Fast-DTW (Fast-Dynamic Time Warping) algorithm was used to assess the skill performance of some karate skills. The results were shown that the percentage of improvement in the skill performance of Mai Geri is 100%.